Health Education Using Lecuter And Leaflet Methods On Knowledge Of Women About Early Detection Of Utery Mioma - Meylani Meylani; Esther Tamunu; Moudy Lombogia; Yourisna Pasambo (Politeknik Kesehatan Makassar, 2020)
Uterine myoma is a benign smooth muscle tumor of the uterus consisting of smooth muscle tissue cells, fibrous binding tissue and collagen located in the uterus. This benign neoplasm is most commonly experienced by women and its prevalence continues to increase by 70%. Myoma uteri can cause big problems in health. Meanwhile, the lack of health information regarding the etiology of myomas has not yet found effective therapy. The importance of health information about early detection of acquired myoma, can increase women's knowledge of the dangers of uterine myoma. The Purpose of this study was to determine the effect of health education with lecture methods and leaflets on early detection of uterine myomas to the knowledge of women in the village of Tateli Dua. This Type of pre experimental design research used one-group pretest-posttest design to compare knowledge before and after health education. The population is women who meet the inclusion and exclusion sample criteria of 65 respondents. The independent variable is health education about early detection of myoma uteri and the dependent variable is women's knowledge. Data collection tools and measuring tools in the form of questionnaires. Data analysis was performed using software and hypothesis testing using the Wilcoxon Signed Rank Test. The test results showed that there was a significant effect of health education using lecture and leaflet methods about early detection of uterine myomas to the knowledge of women in Tateli village (p-value = 0,000 α = 0.05). It was concluded that there was a health education using lecture method and leaflets on early detection of uterine myoma to increase women's knowledge in Tateli Dua village. Keywords : Counseling, Knowledge, Early Detection of Uterine Myoma